Etika Jual Beli Kotoran Sapi dalam Pandangan Islam di Desa Pandanarum Kecamatan Tempeh Lumajang - Umi Suswati Risnaeni; Maisyarofah Maisyarofah (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
Islam is the only perfect religion that governs all human life and the universe including human economic activities are also regulated in Islam with the Divine principle. In the world of business, in Indonesia there is often a sale and purchase of dirt, while animal waste is basically a dirty object that is not desirable, but with the advancement of science and technology, it turns out that animal dung has many benefits. Based on the above facts, the author wants to examine and discuss and know the problem and then compiled it into a scientific work entitled: